A Bibliometric Analysis of Activity-Based Management (ABM) Research Development Using Vosviewer: Management Accounting - Febriani, Erni (UNKLAB Business School, 2024)
This study is a bibliometric visualization by taking journals through the publish or perish application with the scope of data in Scopus about Activity-Based Management (ABM) using the VOSviewer application. The purpose of the bibliometric analysis in this study is to determine; 1) the trend of development of publications related to activity-based management in developed countries each year, 2) the trend of Publication Journals, 3) collaboration between researchers with similar topics, 4) trend terms title and abstract and 5) trend terms author keywords. Data were collected from the Publish or Perish database published in 2010-2024 using the keyword